Comparison of Clinical Diagnosis of Stroke with Computed Tomographic Scan of the Brain - Islam, Sirajee Shafiqul; Rahman, Aminur; Alahi, Md Manzur; Ali, Md Ahmed; Kafiluddin, Md; Kafiluddin, Md; Amin, Md Pervez; Ahmad, Quamruddin; Elyas, Dewan Md; Karim, Md Ziaul; Wadud, Mohammad Shaheen; Islam, Md Rafiqul (Bangladesh Journal of Neuroscience, 2013)
Background and purpose: Stroke is a leading cause of mortality and morbidity in both developed as well as developing countries. The clinical presentation of stroke depending on the site and extent of lesions. For the management purpose it is important to know whether we are dealing with a bleed or an infarct. Methodology: Computed Tomography (CT scan) is available most of the tertiary level hospitals in Bangladesh. This study was carried out to compare clinical diagnosis of stroke with Computed tomography (CT) scan findings in ascertaining the type of stroke (hemorrhagic or ischemic). Materials and methods: This cross-sectional comparative study was conducted in the Department of Neurology, Rajshahi Medical College Hospital during the period of January 2010 to December 2010. Total 200 stroke patients were selected by purposive sampling technique on the basis of inclusion and exclusion criteria as the study sample. . CT brain scan was done for all the patients. The clinical diagnosis was compared with the results of CT scan and performance test was done. Results: Clinically 67 patients were diagnosed as hemorrhagic stroke and 133 patients were diagnosed as ischemic stroke. Out of these 67 hemorrhagic patients CT scan revealed that 56 patients had intracerebral hemorrhage, 5 had infarct, 4 had subarachnoid hemorrhage and 2 had space occupying lesions in the brain. Out of these 133 ischemic patients CT scan revealed that 119 patients had infarction, 6 had intracerebral hemorrhage and 8 had space occupying lesions in the brain. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of clinical diagnosis of hemorrhagic stroke were 90.32%, 92.03%, 83.58%, 92.02% and 91.5% respectively. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of clinical diagnosis of ischemic stroke were 95.96%, 81.58%, 89.47%, 92.53% and 90.5% respectively. Conclusion: The diagnosis of stroke in clinically with high accuracy, but perform a CT scan will help to confirm and differentiate to type stroke. Thus CT scan should be done in all cases stroke to specify the diagnosis. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17179 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 96-101